Impact of Artificial Intelligence (Chatgpt and Google-Bard) on Undergraduates’ Creative Writing Skills at A University in Northeastern Nigeria - Salihu, Abubakar; Aliyu, Muhammad Mukhtar; Nurchalis, Nur Fadillah (Inspiring: English Education Journal, 2024)
Artificial intelligence (AI) has a profound influence on various facets of modern-day society, notably within the realm of education. Its application in educational settings is extensive, primarily aimed at improving the methods of instruction and knowledge acquisition. Thus, this research investigates the impact of AI tools (ChatGPT, Google Bard) on the creative writing skills of Nigerian undergraduates using a pretest-posttest quasi-experimental research design. Eighty (80) third-year undergraduates participated in the study. Data were collected using pretest-posttest writing tasks. The writing scripts were graded using creative writing assessment rubrics. Paired sample t-test analysis was conducted to compare the pretest-posttest writing scores using SPSS. The results of the analysis showed a significant improvement in the participants’ overall writing scores after using the AI tools. The results also show significant improvement in all the aspects of creative writing: image, voice, characterization and story. Finally, the study makes some recommendations for practice and further studies.